Magnetic resonance spectroscopy in myocardial disease. - Hudsmith, L; Neubauer, S (2009)
Magnetic resonance spectroscopy (MRS) is the only noninvasive, nonradiation exposure technique for the investigation of cardiac metabolism in vivo. MRS uses magnetic resonance signals from nuclei, such as (31)phosphorus, (1)hydrogen, and (23)sodium, to provide comprehensive metabolic and biochemical information about cardiac muscle. This method is highly versatile and can provide metabolic insights into the role of cardiac metabolism, in particular, cardiac energetics, in a wide number of conditions, including hypertensive, valvular, and ischemic heart disease, heart failure, and cardiac transplantation, as well as cardiomyopathies. This method can also be used to monitor patient responses to therapeutic interventions: pharmacologic, surgical, or interventional. When combined with cardiovascular magnetic resonance imaging, MRS enables detailed pathophysiologic insights into the inter-relations among cardiac structure, function, perfusion, and metabolism. However, MRS is currently used primarily as a research tool because of low temporal and spatial resolution and low reproducibility. It is hoped that future technical developments and use of higher magnetic field strengths (such as 7-T) may enable application of cardiac MRS in clinical practice.